A global evaluation of musculoskeletal injuries and associated risk factors in competitive aerobic and artistic gymnasts: a systematic review and meta-analysis - Li, D.; Liu, Y.; Liu, Y. (The Journal of Sports Medicine and Physical Fitness, 2026)
INTRODUCTION: Gymnastics has been reported to have one of the highest injury rates in sports, limiting participation and often involving significant medical costs. The current systematic review and meta-analysis research aimed to conduct a critical appraisal of the epidemiological literature on injury patterns and associated risk factors in competitive aerobic and artistic gymnasts.